ANALYSIS OF INTROVERT STUDENTS’ DIFFICULTIES IN SPEAKING ACTIVITIES CLASS AT SMP NEGERI 2 SUNGGUMINASA - Utami R, Maulidya; G, Hasriani; Fauzan, Muhammad Miftah (Universitas Negeri Makassar, 2025)
This study aims to determine the difficulties of introverted students in speaking activities using English. The method used is qualitative with a class observation research design with 6 samples from class VIII, using a purposive sampling technique. Researchers used observation, interview, and documentation methods as research instruments to obtain data. The results of the data analysis show some of the difficulties that introverted students feel in speaking activities in the classroom and the strategies they use to overcome their difficulties in speaking activities including dialogue, presentation, and discussion groups. The proof is based on the results of the interview transcripts from the sample and is reinforced by some previous literature. It is concluded that introverted students at SMP Negeri 2 Sungguminasa experience difficulties in every English-speaking activity in the classroom but they also have their strategies to reduce the difficulties felt.